KEWAJIBAN ANGGOTA MEMBAYAR CICILAN PINJAMAN PADA KREDIT UNION KHATULISTIWA BAKTI DALAM PERJANJIAN DI BAWAH TANGAN PINJAM MEMINJAM DI PAHAUMAN KABUPATEN LANDAK. - NIM. A1012191045, METODEUS KARETO (Fakultas Hukum Universitas Tanjungpura, 2026)
Borrowing and lending at Credit Union (CU) is one of the conventional businesses that has been widely utilized by community members who need the necessary funds as done by some communities in Pahauman, Landak Regency. Credit Union (CU) Khatulistiwa Bakti is a microfinance institution in the form of a legal cooperative based in West Kalimantan, founded on May 12, 1985. In the activity of providing loans to its members with relatively cheap interest of around 1.25% decreasing per month for educational loans and 2% decreasing interest per month for loans such as business capital and agriculture. The amount of the loan is usually limited according to the ability to return interest and installments to members of the Credit Union (CU) Khatulistiwa Bakti. Which is of course for certain purposes, according to the economic conditions and capabilities of the community in Pahauman District who have jobs such as farmers, planters, fishermen, entrepreneurs, and civil servants, where their purpose for borrowing from the Credit Union (CU) Khatulistiwa Bakti is to be used as appropriate. Therefore, the research question is,